Закономірності і проблеми посткомуністичних трансформацій: пострадянський досвід. (Zaporizhzhia Historical Review, 2021)
The article concerns the problem of transformation of political systems of post-socialist countries. The revolutionary reversal and the end of authoritarian regime in the society always result in democratic consolidation. This is the logic of democratic transit. However, experience of post-socialist countries does not coincide with scientific schemes and brings its own peculiarities into the process of post-communist transformations. The analysis of this process is vital and it contributes to the search and determination of optimal solutions of existing and potential future problems as well as to definition of prospects and further development.